Gastrostomy Tubes in Trauma Patients - Lin, Yuan-Mao; Chan, Johanna L.; Murthy, Ravi; Huang, Steven Y. (Digestive Disease Interventions, 2025)
Gastrostomy tubes provide essential long-term enteral nutritional support for trauma patients unable to tolerate oral intake or if prohibited due to associated injuries. This review aims to explore the indications and special considerations unique to gastrostomy tube placement and management for patients following trauma. The specific special considerations addressed in this article are timing of gastrostomy tube placement, timing of gastric tube feeding, technique, indications for postpyloric feeding tubes, concomitant corticosteroid use, safety in patients with an open abdomen, overcoming an inability to pass a nasogastric tube, and considerations for postgastrostomy tube management.
Keywords: gastrostomy; trauma; nutrition